Analisis Farmakokinetik dan Toksisitas pada Bunga Telang (Clitoria Ternatea): In Silico Study - Erna Yovi Kurniawati; Noor Pramono; Syarief Thaufik Hidayat; Endang Mahati (Jurnal Farmasi Indonesia, 2023)
This study explores the pharmacokinetic and toxicity aspects of Clitoria ternatea, which is well-known in traditional medicine for its promising pharmacological potential. Using computational methods, research seeks to unravel the interaction of active compounds in the human body, predicting not only pharmacokinetic properties but also exploring the correlation between chemical structure and parameters such as lipophilicity and P-glycoprotein substrate status, which improves our understanding of the compound's behaviour. The urgency of this research stems from the need for a safe source of therapeutics. Through in-depth in silico toxicity assessments, potential side effects of compounds are carefully identified, ensuring a comprehensive safety evaluation. This important step lays the foundation for responsible pharmacological development. This research introduces a new perspective on exploring traditional medicinal plants, emphasising the importance of safe therapeutic alternatives. The ultimate goal is to establish a solid foundation to further develop C. ternatea as a valuable resource for pharmacological applications and advance natural medicine. The results revealed many compounds with significant pharmacological potential, which show promise for future natural medicine applications. However, the imperative for additional research and experimental validation underscores our commitment to understanding the pharmacological and toxicological aspects of these compounds.